The Biological Action of Some Natural Additives - Rajaa K. Baqir (Journal of Global Pharma Technology, 2018)
Since ancient times humans have been keen to improve their food taste by using natural or processed additives for example in Iraq people used to add stachys pseudopinardii to legumes and use of seidlitzia rosmarinus instead of sodium bicarbonate in the preparation of legumes and add Rhus coriaria to entremets and meat. This study investigated the anti-microbial activity of aqueous extract of the three plants against some bacteria and fungus 100, 500, 1000 mg/mL were the concentration which used in this study, Rhus coiaria has the highest activity than stachy pseudopinardii finally Seidlitzia romarinus.Keyword: Natural additives, biological, activity, bacteria, fungus.